Effects of a novel, transdiagnostic Ecological Momentary Intervention for prevention, and early intervention of severe mental disorder in youth (EMIcompass): findings from an exploratory randomized controlled trial - Reininghaus, Ulrich; Pätzold, Isabell; Rauschenberg, Christian; Hirjak, Dusan; Banaschewski, Tobias; Meyer-Lindenberg, Andreas; Böhnke, Jan R.; Boecking, Benjamin; Schick, Anita (Schizophrenia bulletin, 2023)
Digital interventions targeting transdiagnostic mechanisms in daily life may be a promising translational strategy for prevention and early intervention of psychotic and other severe mental disorders. We aimed to investigate the feasibility and initial signals of efficacy of a transdiagnostic, compassion-focused, hybrid ecological momentary intervention for improving resilience (ie, EMIcompass) in youth with early mental health problems. In an exploratory, assessor-blind randomized controlled trial, youth aged 14-25 with current distress, broad at-risk mental state, or first episode of severe mental disorder were randomly allocated to experimental (EMIcompass+treatment as usual [TAU]) or control condition (TAU). Data on primary (stress reactivity) and secondary candidate mechanisms as well as candidate primary (psychological distress) and secondary outcomes were collected. Criteria for the feasibility of trial methodology and intervention delivery were met (n = 92 randomized participants). No serious adverse events were observed. Initial outcome signals were evident for reduced momentary stress reactivity (stress×time×condition, B = −0.10 95%CI −0.16-−0.03, d = −0.10), aberrant salience (condition, B = −0.38, 95%CI −0.57-−0.18, d = −0.56) as well as enhanced momentary resilience (condition, B = 0.55, 95%CI 0.18-0.92, d = 0.33) and quality of life (condition, B = 0.82, 95%CI 0.10-1.55, d = 0.60) across post-intervention and 4-week follow-up. No outcome signals were observed for self-reported psychological distress (condition, B = 0.57, 95%CI −1.59-2.72, d = 0.09), but there was suggestive evidence of reduced observer-rated symptoms at the 4-week follow-up (B = −1.41, 95%CI −2.85-0.02, d = −0.41). Our findings provide evidence of feasibility and initial signals that EMIcompass may reduce stress reactivity and improve quality of life. A definitive trial is now warranted.
Veröffentlicht: 4. Februar 2023
Gesehen am 31.07.2024